Insights into Reaction Conditions for Selective Catalytic Reduction of NOx with a MnAl Oxide Catalyst at Low Temperatures - Hongjian Zhu; Luming Qiu; Rui Wang (Aerosol and Air Quality Research)
Abstract MnOx catalysts have been proven to have superior activity at low temperatures (LT) for selective catalytic reduction (SCR) of NOx. In this study, spherical mesoporous MnAlx catalysts with different molar ratios were prepared using a simple precipitation method. In addition, their NOx catalytic performance, along with relevant main factors (reaction temperature, molar ratio, particle size, space velocity, and O2 content), was investigated in a simulated fixed bed reactor. The relationship between the main factors and DeNOx efficiency was evaluated by analyzing two parameters: the NOx conversion rate and N2 selectivity. The results showed that the MnAl0.1 catalyst had the optimal low temperature DeNOx performance and had a relatively stable NOx conversion rate of more than 92% in a space velocity range of 14331 h−1 to 23885 h−1, where smaller catalyst particle size led to higher NOx conversion rate and N2 selectivity as high as 100%. In addition, the appropriate oxygen concentration was found to increase NOx conversion and N2 selectivity. This work would be beneficial to further optimization of LT SCR catalyst systems for practical applications.